2014
DOI: 10.1111/jep.12107
|View full text |Cite
|
Sign up to set email alerts
|

Infusion phlebitis assessment measures: a systematic review

Abstract: Rationale, aims and objectivesPhlebitis is a common and painful complication of peripheral intravenous cannulation. The aim of this review was to identify the measures used in infusion phlebitis assessment and evaluate evidence regarding their reliability, validity, responsiveness and feasibility.MethodWe conducted a systematic literature review of the Cochrane library, Ovid MEDLINE and EBSCO CINAHL until September 2013. All English-language studies (randomized controlled trials, prospective cohort and cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
129
2
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(140 citation statements)
references
References 93 publications
3
129
2
6
Order By: Relevance
“…In recent years, studies suggest that the recommendation may need to be revised in lieu of the improved in catheter design and composition. On the other hand, based on level 1 evidence, the most recent Infusion Nursing Standards of Practice and the EPIC3 National Evidence Based Guidelines recommend that short peripheral catheters should be replaced when clinically indicated, unless the patient is receiving parenteral nutrition peripherally [15,16]. The projected 5-year savings from implementing clinically indicated peripheral intravenous catheter removal policies is US$300 million and 1 million health-worker hours in the United States alone [17,18].…”
Section: Review Of Literaturementioning
confidence: 99%
“…In recent years, studies suggest that the recommendation may need to be revised in lieu of the improved in catheter design and composition. On the other hand, based on level 1 evidence, the most recent Infusion Nursing Standards of Practice and the EPIC3 National Evidence Based Guidelines recommend that short peripheral catheters should be replaced when clinically indicated, unless the patient is receiving parenteral nutrition peripherally [15,16]. The projected 5-year savings from implementing clinically indicated peripheral intravenous catheter removal policies is US$300 million and 1 million health-worker hours in the United States alone [17,18].…”
Section: Review Of Literaturementioning
confidence: 99%
“…6 SPCs are often described as the most commonly used VAD in health care. 6,8,32 Peripherally Inserted Central Catheters…”
Section: Short Peripheral Cathetersmentioning
confidence: 99%
“…[1][2][3]27,32,43 Reported rates of SPC-associated phlebitis vary widely among different populations of patients and are often not comparable because of variations in the definition of phlebitis. 2,3,6 Phlebitis may develop up to 48 hours after an SPC is removed.…”
Section: Short Peripheral Cathetersmentioning
confidence: 99%
“…However, the studies report rates between 7% and 68.9% (Abolfotouh et al, 2014;Oliveira, 2014;Pasalioglu & Kaya, 2014;Webster et al, 2015). The variability of results concerning phlebitis incidence may be due to the lack of consensus on the measures used for assessing phlebitis, preventing the meaningful comparison of phlebitis rates (Ray-Barruel et al, 2014). Thus, the use of quality indicators seems to be important to improve the quality of care in order to monitor, measure, and compare, both internally and externally, the obtained results.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic literature review identified 71 scales for phlebitis assessment. However, not all of them were analyzed in psychometric studies, which may lead to differences in the incidence of phlebitis, hampering comparison (Ray-Barruel, Polit, Murfield, & Rickard, 2014). According to the same study, the most widely used phlebitis scales are the Phlebitis Scale, the Visual Infusion Phlebitis, the Baxter Scale, and the Maddox Scale (Ray-Barruel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%